ANALISIS POTENSI KETERSEDIAAN AIR TANAH SECARA SPASIAL UNTUK PEMENUHAN KEBUTUHAN AIR BAKU DI DAS RONTU - Lugina, Izma Maulana Ahmad; Fahmi, Syahrial; Karim, Rizal Aldian; Ismail, Arif (J SIG (Jurnal Sains Informasi Geografi), 2023)
Clean water supply is one of the strategic issues in Bima City which is of concern and is stated in the Bima City RPJMD. The main problem with providing clean water in Bima City is the crisis that occurs when the dry season arrives. Apart from that, if we follow the projected population growth of Bima City, the amount of raw water that is available and can be used as a source of clean water will not be able to meet the needs of the population in the future, so another alternative source is needed, namely by utilizing groundwater. This research aims to spatially see the groundwater potential in the Rontu watershed located in Bima City and measure projected water use needs in the Bima City area. The method used is spatial analysis with quantitative methods Multi Criteria Evaluation (MCE), Groundwater Potential Index (GWPI), and the Thornthwaite method for determining areas that have the potential to have groundwater. The research uses the help of a geographic information system (GIS) and remote sensing data to produce a groundwater potential zone map. Based on the results of the groundwater potential zoning map created, it can be seen that the Rontu watershed area as a whole and Bima City tend to have very high potential for groundwater storage and supply. This research also provides an overview of water use in both the domestic and non-domestic sectors in the Rontu Watershed area which includes Bima City and calculates the remaining water reserves from the results of water use and water supply obtained in the Rontu Watershed area, so that it can provide recommendations. for future water supply.